The Implementation of Karate Martial Arts Learning According to The Pjok Curriculum at Junior High Schools in East Telukjambe District - Muhammad Antoni Febriansyah; Resty Gustiawati; Siswanto (Jurnal Pendidikan Jasmani (JPJ), 2022)
This study aims to determine the implementation of martial arts learning in junior high schools in east Telukjambe district. This research is a quantitative descriptive research. The method used in this study was a survey. The instrument used in this study was a questionnaire with a reliability of 0.977. The subjects in this study were physical education teachers in the east telukjambe sub-district as many as 7 teachers. Data analysis or data processing techniques use the Respondent Achievement Rate (TCR). The results of the study found that the implementation of karate martial arts learning in accordance with the PJOK curriculum in junior high schools in east telukjambe district was in the very low category of 46.72% in terms of 6 indicators, learning preparation indicators of 57.70% in the low category, learning process indicators of 42.85% in the very low category, learning evaluation indicators of 45.71% in the very low category, facilities and infrastructure indicators 47.99% very low category, time allocation indicators 42.13% very low category, curriculum indicators 43.99% very low categories. This shows that the implementation of karate martial arts learning in junior high schools in east telukjambe district has not been carried out as it should be.